Implementation of The Citizen Services Information System RW 016 Kapuk West Jakarta City - Hidayat, Farasya Syifa; Rusdi, Zyad; Perdana, Novario Jaya (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
The advent of e-government in Indonesia, initiated by the Presidential Instruction in 2003, has paved the way for the digital transformation of governmental services at both national and regional levels. This research focuses on the utilization of this transformation by Rukun Warga (RW) 16, Kapuk Village, West Jakarta, demonstrating a shift towards digital-based administration in local governance. The study aims to facilitate more efficient and effective communication and information dissemination between the RW.16 administrative body and its residents. The deployment of the proposed application is expected to streamline public service processes by providing residents with comprehensive access to various public services information specific to RW.16. Furthermore, the application empowers residents to submit letters, express their aspirations, and report environmental issues directly to the RW.16 management, thereby enabling prompt resolution of these concerns. The application's development adhered to the System Development Life Cycle (SDLC) using the waterfall methodology, ensuring a structured and sequential approach. The backend database is built on MySQL, while the front-end interfaces are developed using HTML and PHP, supported by the Laravel framework. This study highlights the potential of e-government initiatives in enhancing public service delivery and community engagement.